Medical tourism: experiences of international patients seeking inpatient treatment for anorexia nervosa at Akeso Montrose Manor - Aron, Lauren (Department of Social Development, 2021)
This study explored the concept of medical tourism and the subjective experiences of international patients seeking inpatient eating disorder (ED) treatment at a private inpatient ED clinic in South Africa. This research aimed to shed light on what patients with Anorexia Nervosa (AN) feel are essential features of a high-quality ED service at Akeso Montrose Manor specifically, and what they found to be concerning about ED treatments received prior, especially in the United Kingdom. The research aimed to explore the participant's reasons for seeking treatment at Akeso Montrose Manor, their expectations of treatment, their experience of treatment and their recommendations regarding the treatment of international patients. Ex-patients from the United Kingdom were chosen for this study, as a high number of admissions for treatment at Akeso Montrose Manor are from the United Kingdom. This therefore provoked an interest in exploring the reasons why these patients search for specialised out-of-country treatment. The research was conducted using a qualitative research design. Twenty participants were selected using purposive sampling by the researcher. They were interviewed face-to-face and via Skype using a semi-structured interview schedule. The data obtained was analysed using qualitative methods. The findings of this study highlighted several difficulties experienced in the United Kingdom when seeking treatment and also highlighted the value of residential inpatient treatment centres, extended treatment for ED's and the importance of specialised ED treatment teams and units. The results included that participants came to South Africa, due to challenges experienced in accessing treatment in the United Kingdom and treatment largely being dictated by weight and focused mostly on weight restoration. Expectations met during their stay in South Africa, included structure, safety and specialised ED treatment and staff and expectations not met whilst in treatment at Akeso Montrose Manor included limited time with the dietician and psychiatrist, and their belief that they would be fixed post-discharge. Participants made recommendations for the clinic with regards to the treatment of international clientele, which included more focus on post discharge planning and support. Further recommendations were made for improved service delivery at Akeso Montrose Manor as well as further research.